An outcome analysis of videoscopic assisted retroperitoneal debridement in infected pancreatic necrosis: a single centre experience - Budkule, Dattaraj (Turk J Surg, 2019)
OBJECTIVES: Infected pancreatic necrosis (IPN) is a dreadful complication of moderately severe and severe acute necrotising pancreatitis (ANP). Videoscopic assisted retroperitoneal debridement (VARD) is a minimally invasive surgical option for predominantly left sided, posterior and laterally located disease in patients not responding to conservative and percutaneous options. This study aimed to present an outcome analysis of VARD in the management of IPN at our tertiary care centre. MATERIAL AND METHODS: The present retrospective analysis of prospectively entered data included 22 patients diagnosed as ANP with IPN from January 2015 to December 2017. These patients were admitted in the surgical gastroenterology unit of our tertiary care centre. The outcome of these patients managed with VARD was evaluated. RESULTS: The aetiology of ANP was idiopathic, and gallstones were found in 7 patients each and alcohol in 8. Twelve patients were managed with a single VARD procedure; whereas, 10 required a re-debridement due to suboptimal improvement. Eighteen out of 22 patients survived whereas 4 succumbed to major postoperative bleeding/severe sepsis and multiorgan failure (Mortality 18.2%). Hospital stay after the index procedure was between 6 to 11 weeks. CONCLUSION: VARD is a safe and effective surgical option for the management of IPN that worsens or fails to respond to conservative and percutaneous drainage options after a minimum of 4 weeks of moderately severe and severe ANP. It decreases postoperative morbidity and mortality and avoids major laparotomy, and hence, it can be considered in a selected group of patients.